Implementasi Fitur Keamanan dengan JSON Web Token dan Fitur Geo-tagging pada Aplikasi Web Service Training From Home - Aal Hibsy; Arief Wibowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
In the Covid-19 pandemic phase, some business processes were halted, adapted, and modified to deal with the policy of social restrictions. This impact is experienced by all levels of society, including athletes who are forced to do training from home (Training From Home). Performance evaluation of athletes who do exercises from home must be able to be evaluated remotely, including in terms of presence during the exercise training program. Presence is one of the benchmarks of a person's level of performance or activity in terms of accuracy and discipline in a program of activities. Attendance activities in the form of check-in must be ensured safe and accurate, especially if there is data connectivity with the webserver. This study aims to implement security features with JSON Web Token (JWT) based on the 256 Hash algorithm. The research also implements geo-tagging features to obtain accurate coordinates based on location points. Athlete attendance data obtained by the presence of these features are then synchronized via web service using the REST architecture. All stages of implementation are then tested by the Black Box method, and the results show that JSON Web Token (JWT) is able to secure the authentication and data security process, while the Geo-tagging feature is capable of sending accurate position data. Testing the functionality of the web service shows that all features work well within 44.8 ms, while the positioning accuracy of the geo-tagging feature reaches an accuracy of 90.9%.